2008
DOI: 10.1152/ajpheart.01023.2008
|View full text |Cite
|
Sign up to set email alerts
|

Limited functional and metabolic improvements in hypertrophic and healthy rat heart overexpressing the skeletal muscle isoform of SERCA1 by adenoviral gene transfer in vivo

Abstract: O'Donnell JM, Fields A, Xu X, Chowdhury SA, Geenen DL, Bi J. Limited functional and metabolic improvements in hypertrophic and healthy rat heart overexpressing the skeletal muscle isoform of SERCA1 by adenoviral gene transfer in vivo. Am J Physiol Heart Circ Physiol 295: H2483-H2494, 2008. First published October 24, 2008 doi:10.1152/ajpheart.01023.2008.-Adenoviral gene transfer of sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA)2a to the hypertrophic heart in vivo has been consistently reported to lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
33
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 68 publications
(158 reference statements)
11
33
1
Order By: Relevance
“…Surprisingly, we found the overexpression of the SERCA1 isoform actually compromised cardiac performance, in vivo (O'Donnell et al, 2008). Our finding was recently supported by a second report (heart failure model in SERCA2a transgenic mice) (Pinz et al, 2011).…”
Section: Serca Gene Therapy For Heart Failure: Good or Bad?supporting
confidence: 82%
See 4 more Smart Citations
“…Surprisingly, we found the overexpression of the SERCA1 isoform actually compromised cardiac performance, in vivo (O'Donnell et al, 2008). Our finding was recently supported by a second report (heart failure model in SERCA2a transgenic mice) (Pinz et al, 2011).…”
Section: Serca Gene Therapy For Heart Failure: Good or Bad?supporting
confidence: 82%
“…In support of other reports (Chen et al, 2004;Taluker et al, 2007), we found the strategy significantly improved post-ischemic recovery of cardiac function and metabolism in rat (O'Donnell et al, 2009). However, the strategy compromised cardiac function in the hypertrophic heart (O'Donnell et al, 2008). This finding contradicts the earlier reports which used the conventional catheter-based cross-clamp approach to delivery the cDNA for SERCA2a (Miyamoto et al, 2000;Del Monte et al, 2001;Byrne et al, 2008).…”
Section: Routes Of Gene Deliverymentioning
confidence: 63%
See 3 more Smart Citations